PENERAPAN METODE BERMAIN KONSTRUKTIF UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS DAN KREATIVITAS (Studi Pada Anak Kelompok B di TK Negeri 19 Bengkulu Selatan) - Zanirahmabeti Zanirahmabeti; Wasidi Wasidi (UNIB Press, 2020)
The purpose of this study was to describe the application of constructive play methods to improve fine motor skills and creativity in TK Negeri 19 Bengkulu Selatan. This research method is Classroom Action Research (PTK). The subjects of this study were 15 children in group B in TK Negeri 19 Bengkulu Selatan. The data collection technique used teacher observation sheets and children's observation sheets. Data analysis used paired two-sample t test and a success rate of 75%. The results showed that the description of the process of implementing the constructive method in group B at TK Negeri 19 Bengkulu Selatan, it was seen that in the first and second cycles there were still underdeveloped children and only 2 children who have developed well, but in the third cycle it has increased in the absence of undeveloped children. The application of constructive methods through drawing activities can improve the fine motor skills of early childhood in group B at TK Negeri 19 Bengkulu South seen from the second cycle the children have developed according to expectations and there are no children who have not developed and the t test results show that the t value is greater than the t table value. The application of constructive methods is significant in increasing children's creativity, seen from the results of the t test in the second and third cycles, the t value is greater than the t table value